Teachers’ Control System on Negative Impact of Smartphone at Madrasah Ibtidaiyah - Suriana Suriana (Al Ibtida: Jurnal Pendidikan Guru MI, 2019)
AbstractThe proliferation of smartphone which are cheap and easy to obtain, raises a trend among parents to give their children a smartphone. This situation raises the concern about psychological health and student religiosity. The teachers become the only one who can filter the students and equip them with Islamic values. Thus, they are not swallowed up by the swift flow of digital negatives that are not yet fully understood by students. This paper tries to analyze the teachers’ control system in limiting the usage of smartphone and providing a negative and positive understanding on the impacts of smartphones at MIN Darul Imarah of Aceh Besar District. This study uses descriptive qualitative methods. The data colection techniques were observation and interview using triangulation for data validity and realibility. The results show that teachers at MIN Darul Imarah sub-district of Aceh Besar, control the use of the negative impact of smartphone on their students by means of; limiting smartphone usage by prohibiting students from taking cellphones to shcool and giving punishmet to those who violate these rules. Furthermore, in providing understanding to students, the teachers do explaining the negative and positive impacts of smartphones in both inside and outside the learning instruction; teaching how to use smartphones smartly; using religious approaches; linking subject matter to the negative impact of smartphones; and socializing the negative impact of smartphones.Keywords: controlling, smartphones, student of Madrasah Ibtidaiyah.AbstrakMenjamurnya smartphone yang murah dan mudah diperoleh, menimbulkan tren di kalangan orang tua untuk memberikan smartphone kepada anaknya. Keadaan ini menimbulkan kekhawatiran terhadap kesehatan psikis dan religiusitas siswa. Guru menjadi satu-satunya harapan untuk dapat memfilterisasi siswa dan membekali siswa dengan nilai-nilai Islam. Hal ini diperlukan untuk meminimalisir derasnya arus negatif digital yang belum sepenuhnya dipahami oleh siswa. Tulisan ini berusaha menganalisis sistem kontrol guru dalam membatasi pemakaian dan memberikan pemahaman akan dampak negatif dan positif smartphone pada siswa MIN di Kecamatan Darul Imarah Kabupaten Aceh Besar. Kajian ini menggunakan metode kualitatif deskriptif, dengan menggunakan teknik observasi dan wawancara dengan menggunakan triangulasi data dalam memvaliditas data. Hasilnya menunjukkan bahwa guru MIN se-kecamatan Darul Imarah Aceh Besar dalam mengontrol pemakaian dampak negatif teknologi komunikasi pada siswanya dengan cara melarang siswa membawa handphone ke madrasah dan memberikan punishmet apabila aturan tersebut dilanggar. Selanjutnya, dalam memberikan pemahaman kepada siswa, guru melakukan dengan cara menjelaskan dampak negatif dan positif smartphone baik di dalam maupun di luar pembelajaran, mengajarkan cara menggunakan smartphone secara cerdas, menggunakan pendekatan religius, mengaitkan materi pelajaran dengan dampak negatif smartphone, mensosialisasikan dampak negatif smartphone kepada orang tua siswa, serta mengadakan program pengembangan kreatifitas siswa.Kata kunci: pengawasan, smartphone, siswa, madrasah ibtidaiyah.